Pengembangan Modul Ajar Berbasis Pembelajaran Berdiferensiasi Pada Materi Matriks - Nursantriana, Nursantriana; Rusli, Rusli; Hamda, Hamda (Universitas Cokroaminoto Palopo, 2025)
This study aims to describe the development process, show specifications, assess the quality, and determine the effectiveness of teaching modules based on differentiated learning on matrix material. The type of research used is Research and Development which refers to the ADDIE model which consists of five stages namely Analysis, Design, Development, Implementation, and Evaluation. The subjects of this trial were students of class XI SMA Negeri 21 Makassar. The results showed that the assessment by validators on teaching modules and research instruments received an average score of 4,31 with valid criteria. The results of the data analysis of the students' response questionnaire to the teaching module showed very positive criteria in trial I with a percentage of 87,9 and trial II with a percentage of 91,9%, the teacher's response questionnaire to the teaching module showed very positive criteria in trial I with a percentage of 86,1% and trial II with a percentage of 94,4%, and the learning implementation observation sheet showed the criteria were fully implemented in trial I with a percentage of 1,8 and trial II with a percentage of 1,9 so that the teaching module was declared practical. The results of data analysis of student activity sheets showed very active criteria in trial I with a percentage of 85,2% and trial II with a percentage of 87,2%, the learning outcomes test reached 80% in trial I and 100% in trial II, so that the teaching module was declared effective. Referring to the results of the analysis, it can be concluded that the teaching module based on a differentiated learning on matrix material can be used in learning activities.